Caldesmon: Biochemical and Clinical Implications in Cancer - Yao, Yi-Bo; Xiao, Chang-Fang; Lu, Jin-Gen; Wang, Chen (Frontiers in Cell and Developmental Biology, 2021)
Caldesmon, an actin-binding protein, can inhibit myosin binding to actin and regulate smooth muscle contraction and relaxation. However, caldesmon has recently attracted attention due to its importance in cancer. The upregulation of caldesmon in several solid cancer tissues has been reported. Caldesmon, as well as its two isoforms, is considered as a biomarker for cancer and a potent suppressor of cancer cell invasion by regulating podosome/invadopodium formation. Therefore, caldesmon may be a promising therapeutic target for diseases such as cancer. Here, we review new studies on the gene transcription, isoform structure, expression and phosphorylation regulation of caldesmon and discuss its clinical implications in cancer.